2009
DOI: 10.17221/944-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lactoferrin in Goat Milk by HPLC Method

Abstract: Abstract:The aim of this study was the determination of lactoferrin in goat milk using HPLC method. Milk samples were collected at a goat farm in the South Moravia Region, the Czech Republic. It were established bulk tank samples of raw milk (n = 24) and pasteurised milk (n = 27) that were collected during lactation. Lactoferrin contents were analysed by reverse phase high-performance liquid chromatography (RP-HPLC) with diode-array detector PDA 2996. Detection was carried out at the wavelength 205 nm. The ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 5 publications
(5 reference statements)
0
16
0
2
Order By: Relevance
“…Similar results for lactoferrin stability in raw goat's milk were reported by Dračková et al . (). The authors observed maximum lactoferrin concentration in colostrum, while over the following weeks the concentration decreased.…”
Section: Resultsmentioning
confidence: 97%
“…Similar results for lactoferrin stability in raw goat's milk were reported by Dračková et al . (). The authors observed maximum lactoferrin concentration in colostrum, while over the following weeks the concentration decreased.…”
Section: Resultsmentioning
confidence: 97%
“…Продукция рчЛф с моло-ком коз составила до 10 г/л [44][45][46]. Важно отметить, что козы не имеют общих с человеком заболеваний.…”
Section: обоснования к использованию лактоферрина у детей с сепсисом unclassified
“…The eluted protein was dialyzed against PBS containing decreasing concentration of urea. Purity of the recombinant Lf was checked by HPLC following the method of Drakova et al (2009).…”
Section: Purification Of the Recombinant Lactoferrinmentioning
confidence: 99%